Loan Loss Provision Behaviours in Chinese Commercial Banks from year 2012 to 2018 - Qi, Chunyi (2019)
On the strength of the investigation in situation of Chinese banking industry, this dissertation uses the experimental research to explore the four main hypotheses on loan loss provisions of Chinese commercial banking system during 2012 and 2018. A dynamic unbalanced panel dataset of different variables of 172 Chinese commercial banks are selected and investigated by applying IV-GMM, which represents instrumental variables and the Generalized Method of Moments (GMM) methodology. X-efficiency data will be generated from SFA model. The relevant theories about income smoothing, capital management, business cycle and efficiency are confirmed by empirical research within different significance level and the empirical results are analyzed. Chinese commercial banks should put more emphasis on overall planning and coordination in regulation, and continue to precaution and deal with financial risks in key areas. And a dynamic provisioning system should be established and promoted.